High-precision 3D printing of high-strength polymer-derived ceramics: impact of precursor's molecular structure - Chen, Hui (2022)
Additive manufacturing (3D printing) offers new opportunities to create complex structures for many applications. The development of suitable precursors for high-resolution 3D printing of ceramics is increasingly essential to meet evolving material requirements. Herein, a new hybrid preceramic formulation based on thiol-ene click chemistry for precision printing of polymer-derived ceramic has been developed to enable the fabrication of complex 3D objects using high-resolution projection microstereolithography (PμSL). Two low-odor thiol compounds with either three (trithiol) or four thiols (tetrathiol) moieties have been examined, to investigate the influence of thiol structure on the mechanical properties of converted ceramics. Pyrolysis of the printed green bodies leads to the formation of silicon oxycarbide (SiOC) with high fidelity after polymer-to-ceramic transformation. The SiOC printed specimen converted from the tetrathiol formulation (4T) demonstrates excellent mechanical strength surpassing that of the trithiol-based formulation (3T) and previously reported SiOC preceramic polymers. The ceramic honeycomb fabricated using the tetrathiol compound shows remarkable improvement in compressive strength, which is two times higher than that of the trithiol-derived ceramic. This work proposes a simple and effective way to formulate 3D printable preceramic polymers through molecular design. The achieved 3D printed SiOC can fulfill the requirement for high-strength ceramic materials with complex shapes.